Mass Production of 2D Manifolds of Graphene Oxide by Shear Flow. (1st October 2021) - Choi, Gyeong Min; Park, Minji; Shim, Yul Hui; Kim, So Youn; Lee, Heon Sang
Abstract: Self‐organizing 2D sheets into a 3D structure with a well‐defined arrangement and tuned bandgap has garnered significant interest. However, there exist challenges such as scalable and feasible synthetic methods and preservation of 2D properties while preventing re‐stacking. Herein, a facile method for the mass production of 2D manifolds of graphene oxide (GO), which are 3D microtubes, while maintaining their 2D properties by applying shear to roll up GO sheets, is reported. The GO mesotubes are formed by shear flow in aluminum–glass parallel plates. Redox reaction plays a vital role during the formation of GO mesotubes by the vorticity alignment during slow shear flow. A high yield of 94% is achieved at an initial pH of 2.2. The maximum d ‐spacing of the GO sheet in the tube wall is 21 nm, indicating no re‐stacking of the graphitic structure. It is demonstrated that the GO mesotubes behaves like a soft gel, rendering them a candidate material for soft robotics, e‐skins, and a visible light sensor owing to their reduced optical bandgap. Abstract : The chemical mechanism and GO domain dynamics during shear flow for the mass production of the 2D manifolds of GOs are unveiled. The 2D manifolds are multiwalled GO mesotubes with a GO interlayer spacing of 21 nm. The GO mesotube behaves like a soft gel with Young's modulus of 974 Pa and is robust to 10 5 cycles of bending tests.